Pro-inflammatory effects of inhaled Great Salt Lake dust particles - Jacob M. Cowley; Cassandra E. Deering-Rice; John G. Lamb; Erin G. Romero; Marysol Almestica-Roberts; Samantha N. Serna; Lili Sun; Kerry E. Kelly; Ross T. Whitaker; Jenna Cheminant; Alessandro Venosa; Christopher A. Reilly (Particle and Fibre Toxicology, 2025)
Abstract Background Climate change and human activities have caused the drying of marine environments around the world. An example is the Great Salt Lake in Utah, USA which is at a near record low water level. Adverse health effects have been associated with exposure to windblown dust originating from dried lakebed sediments, but mechanistic studies evaluating the health effects of these dusts are limited. Results Monitoring data and images highlight the impact of local crustal and Great Salt Lake sediment dusts on the Salt Lake Valley/Wasatch front airshed. Great Salt Lake sediment and derived PM< 3.1 (quasi-PM2.5 or qPM2.5) contained metals/salts, natural and anthropogenic chemicals, and bacteria. Exposure of mice via inhalation and oropharyngeal aspiration caused neutrophilia, increased expression of mRNA for Il6, Cxcl1, Cxcl2, and Muc5ac in the lungs, and increased IL6 and CXCL1 in bronchoalveolar lavage. Inhaled GSLD qPM2.5 caused a greater neutrophilic response than coal fly ash qPM2.5 and was more cytotoxic to human airway epithelial cells (HBEC3-KT) in vitro. Pro-inflammatory biomarker mRNA induction was replicated in vitro using HBEC3-KT and differentiated monocyte-derived (macrophage-like) THP-1 cells. In HBEC3-KT cells, IL6 and IL8 (the human analogue of Cxcl1 and Cxcl2) mRNA induction was attenuated by ethylene glycol-bis(β-aminoethyl ether)-N, N,N′,N’-tetraacetic acid (EGTA) and ruthenium red (RR) co-treatment, and by TRPV1 and TRPV3 antagonists, but less by the Toll-like Receptor-4 (TLR4) inhibitor TAK-242 and deferoxamine. Accordingly, GSLD qPM2.5 activated human TRPV1 as well as other human TRP channels. Dust from the Salton Sea playa (SSD qPM2.5) also stimulated IL6 and IL8 mRNA expression and activated TRPV1 in vitro, but inhibition by TRPV1 and V3 antagonists was dose dependent. Alternatively, responses of THP-1 cells to the Great Salt Lake and Salton Sea dusts were partially mediated by TLR4 as opposed to TRPV1. Finally, “humanized” Trpv1 N606D mice exhibited greater neutrophilia than C57Bl/6 mice following GSLD qPM2.5 inhalation. Conclusions Dust from the GSL playa and similar dried lakebeds may affect human respiratory health via activation of TRPV1, TRPV3, TLR4, and oxidative stress.